Poly (butylene adipate-co-terephthalate)/magnesium oxide/silver ternary composite biofilms for food packaging application. (June 2020) - Zhang, Jie; Cao, Chenglin; Zheng, Shaoming; Li, Wei; Li, Baobi; Xie, Xiaoling
Graphical abstract: Highlights: The compounding antibacterial agent composed of nano Ag and MgO was added into the PBAT matrix. The mechanical properties of the nanocomposites were improved. The NPs played as the nucleating agents to improve the crystallization process of the PBAT matrix. The barrier properties of the nanocomposites were suitable for packaging applications. The optimal concentration of Ag/MgO nanoparticles was 3 wt%. Abstract: Poly (butylene adipate- co -terephthalate) (PBAT)/ magnesium oxide (MgO)/ silver (Ag) ternary composite biofilms were prepared via a common solvent casting method and used for food packaging. The effects of MgO/Ag nanoparticles (NPs) on the physical and antibacterial properties of the composite biofilms were comprehensively investigated. The physical properties of the PBAT matrix, such as the mechanical and barrier properties, are improved by the incorporation of MgO/Ag NPs. The composite films with 3 wt% NPs content exhibit the optimal properties. Specifically, the tensile strength, the elongation at break, water barrier property, and oxygen barrier property are 11.91 MPa, 415.63 %, 1.135 kg·m/m²·s·Pa, and 3.679 Barrer, respectively. Furthermore, the inhibition rates of ternary composite film against Escherichia coli and Staphylococcus aureus exceed 90 %, indicating potential for application in the food packaging industry.